Design of the “EAST” strategy in patients with symptomatic intracranial atherosclerotic stenosis - Dai, Jiaqi; Zhao, Haobo; Chen, Xinyu; Nie, Ping; Gong, Jie; Wang, Min; Zhang, Kezhong; Wang, Zhaolu; Lu, Hua (Frontiers in Neurology, 2025)
IntroductionThere is a high risk of stroke occurrence and recurrence in patients with intracranial atherosclerotic stenosis (ICAS) despite aggressive medical therapy. Evolocumab is a monoclonal antibody which can inhibit proprotein convertase subtilisin-kexin type 9 (PCSK9) and effectively reduce the level of low-density lipoprotein cholesterol. We hypothesize that evolocumab added to statin therapy (EAST) can stabilize intracranial plaques in patients with symptomatic ICAS.Methods and analysisThis is a prospective, randomized, open-label, blinded end-point study, which will assess the efficacy and safety of evolocumab in patients with symptomatic ICAS. Eighty patients who suffer a stroke/transient ischemic attack (TIA) caused by ICAS recently will be randomly allocated in a 1:1 ratio to the evolocumab plus statin treatment group or the statin treatment group. High resolution vessel wall magnetic resonance imaging (HR-vwMRI) will be performed at recruitment and after 6 months and 12 months. The primary outcome is changes in plaque characteristics assessed by HR-vwMRI at 6th month and 12th month after treatment. Cognitive and neurological function will also be evaluated at recruitment and follow-up. This trial is being conducted at the first affiliated hospital of Nanjing medical university, China.Ethics and disseminationAll participants will sign written informed consents. Peer-reviewed articles will be published to disseminate study outcomes.Clinical trial registrationClinicalTrials.gov, identifier: NCT05741086.